METHODOLOGICAL STRATEGIES FOR CROSS-LINGUISTIC AND CROSS-CULTURAL ANALYSIS: INSIGHTS FROM ENGLISH– UZBEK COMPARATIVE RESEARCH - Fotima Karimova Kamoliddin qizi (Western European Studies, 2025)
Cross-linguistic and cross-cultural analysis occupies a central place in contemporary comparative linguistics, translation studies, and discourse research. This article proposes a methodological framework tailored to English–Uzbek comparative research, highlighting strategies such as contrastive analysis, corpus-driven methods, mixed qualitative– quantitative designs, discourse and cultural-contextual analysis, and triangulation of findings. Grounded in recent empirical studies of English and Uzbek (phraseology, terminology, and cognitive metaphors), the article synthesizes methodological insights and provides practical guidance for researchers investigating evaluative–expressive communicative signs across languages and cultures. The framework emphasizes the interplay of linguistic structure, cultural worldview, and discourse function
Keywords: cross-linguistic analysis; cross-cultural methodology; English; Uzbek